2020
DOI: 10.1111/epi.16439
|View full text |Cite
|
Sign up to set email alerts
|

Treatment initiation decisions in newly diagnosed epilepsy–A longitudinal cohort study

Abstract: Objective To examine the factors and reasons influencing treatment initiation decisions in patients with newly diagnosed epilepsy. Methods We assessed antiseizure medication initiation decisions in adults with newly diagnosed epilepsy seen at first seizure clinics in Western Australia between 1999 and 2016 and followed to 2018. Results Of 610 patients (median age 40 years, 61.0% male), 426 (69.8%) were diagnosed after two or more seizures and 184 (30.2%) after a single seizure with risk factors for recurrence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 33 publications
0
24
1
2
Order By: Relevance
“…In our study, 51 out 55 (93%) patients with the diagnosis of epilepsy at the long‐term follow‐up were getting treatment with an ASM. This proportion of patients with newly diagnosed epilepsy getting ASM treatment is higher than what has been described in other high‐income countries 12–14 . We do not have a good explanation for this discrepancy but believe this is due to several factors 13 …”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…In our study, 51 out 55 (93%) patients with the diagnosis of epilepsy at the long‐term follow‐up were getting treatment with an ASM. This proportion of patients with newly diagnosed epilepsy getting ASM treatment is higher than what has been described in other high‐income countries 12–14 . We do not have a good explanation for this discrepancy but believe this is due to several factors 13 …”
Section: Discussioncontrasting
confidence: 58%
“…This proportion of patients with newly diagnosed epilepsy getting ASM treatment is higher than what has been described in other high-income countries. [12][13][14] We do not have a good explanation for this discrepancy but believe this is due to several factors. 13 The diagnostic accuracy of EEG after a first unprovoked seizure has been reported to be quite low and a recent review and meta-analysis of published studies suggested a sensitivity and specificity of routine EEG to be 17.3% and 94.7% respectively.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…While previous attempts at the same were done largely through surrogate markers of treatment response, 14, 15, 22 we have the advantage of being able to train our predictive model using relevant clinical information with known standard treatment outcome measures in two large cohorts of newly diagnosed and treated epilepsy patients. 3, 23…”
Section: Limitations and Discussionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic has affected everyone around the world, not least through pressure on healthcare systems and delivery of care. The initial wave and consequent lockdowns led to the cancellation of routine investigations and elective interventions, and many health care providers had to move to alternative models of care delivery [ 1 , 2 , 3 , 4 ]. The new disease started in China in late December 2019 and rapidly spread worldwide, becoming a global pandemic issue [ 1 ].…”
Section: Introductionmentioning
confidence: 99%